Impact of Broadband Quality on Median Income and Unemployment: Evidence from Sweden - Maude Hasbi; Erik Bohlin (International Telecommunications Society (ITS), 2021)
Based on a unique and exhaustive database, including micro-level cross-sectional data on 23 million observations over nine years, from 2009 to 2017, we assess whether broadband quality has an impact on income and unemployment reduction. Overall, the results do not show any significant effect of download speed on either income or the unemployment rate. However, after distinguishing between educational attainment and the city size, we obtained heterogeneous results. While we highlight a substitution effect between low-skilled workers and broadband in smaller cities, we also show that broadband quality has a positive impact on unemployment reduction for low-skilled workers in bigger cities. However, the model predicts a negative effect of broadband quality on both the median income and the unemployment rate in areas having a higher proportion of college graduates. This result tends to support the analyses showing that, with the progress made in machine learning, artificial intelligence and the increasing availability of big data, job computerization is expanding to the sphere of high-income cognitive jobs.
Keywords: L13; L50; L96; 330; Broadband Quality; Fibre; Income; Unemployment; Artificial Intelligence